Inventing Polymer Science : Staudinger, Carothers, and the Emergence of Macromolecular Chemistry - Furukawa, Yasu (Chemical Sciences in Society, 2016)
It would be difficult to overestimate the importance of polymer science to life in the twentieth century. Developments in polymer chemistry and engineering have led not only to the creation of a variety of substances such as synthetic fibers, synthetic rubber, and plastic but also to discoveries about proteins, DNA, and other biological compounds that have revolutionized western medicine. For these reasons, the history of the discipline tells an important story about how both our material and intellectual worlds have come to be as they are. Yasu Furukawa explores that history by tracing the emergence of macromolecular chemistry, the true beginning of modern polymer science. It is a lively book, given human interest through its focus on the work of two of the central figures in the development of macromolecular chemistry, Hermann Staudinger and Wallace Carothers. In Inventing Polymer Science, Furukawa examines the origins and development of the scientific work of Staudinger and Carothers, illuminates their different styles in research and professional activities, and contrasts the peculiar institutional and social milieux in which they pursued their goals.